Patient reported outcome of adult perioperative anaesthesia in the United Kingdom: a cross-sectional observational study - Walker, E.M.K.; Bell, M.; Cook, T.M.; Grocott, M.P.W.; Moonesinghe, S.R. (Oxford University Press, 2016)
Background. Understanding the patient perspective on healthcare is central to the evaluation of quality. This study measured selected patient-reported outcomes after anaesthesia in order to identify targets for research and quality improvement.